Gambaran Kadar Gula Darah dan Tekanan Darah Penderita Diabetes Melitus Tipe 2 di Puskesmas Kalibagor - Azzalia Nur Rahma; Suci Khasanah; Indri Heri Susanti (Pusat riset dan Inovasi Nasional, 2025)
Type 2 diabetes mellitus is a chronic disease caused by metabolic disorders, characterized by impaired insulin secretion and action, with its prevalence continuously increasing. This study aims to describe blood glucose levels and blood pressure in patients with type 2 diabetes mellitus at the Kalibagor Health Center based on respondent characteristics. The method used is descriptive quantitative with a cross-sectional design, involving 50 patients with type 2 diabetes mellitus selected through total sampling technique. Data were collected through random blood glucose tests, blood pressure measurements, and interviews regarding smoking habits and family history. The results showed that 58% of respondents had high blood glucose levels, while 70% had normal blood pressure. Respondents with a family history of diabetes were more likely to experience high blood glucose levels, while smokers had a higher risk of experiencing high blood pressure. This study also found the influence of age, gender, and family history on blood glucose and blood pressure levels. Therefore, further education on healthy lifestyle and risk factor management is needed to prevent further complications in patients with type 2 diabetes mellitus.